Adolescents Level of Perceived Stress and its Relationship with Body Mass Index in a Bangladeshi Population (Journal of Enam Medical College, 2017)
Background: Several behavioral factors, specially stress, eating behavior, and physical activity have been linked with adolescent obesity. In our country, mental health of adolescents is often neglected. So, we designed this study to describe the current perception of stress in Bangladeshi adolescent students.Objective: Aim of this study was to assess association between stress and body mass index of adolescents while controlling for physical activity and examining stress associated eating behavior.Materials and Methods: This cross-sectional study was carried out among 278 adolescent students during the period from January to December 2013. Data were collected through self-administered questionnaire which included physical activity questions, Dutch Eating Behavior Questionnaire (DEBQ), Adolescent stress questionnaire (ASQ) and standard anthropometric measurements and were analyzed statistically using SPSS version 21.0.Results: In this study majority of the respondents were males. Among the female respondents, about 12.23% were overweight and obese compared to their male peers (4.1%). The normal and high BMI adolescents in the study showed significantly different proportions regarding gender (p